MENINGKATKAN PEMAHAMAN DAN KEMAMPUAN MEMECAHKAN MASALAH TENTANG PENGOLAHAN SAMPAH MELALUI PROBLEM BASED LEARNING (PBL) PADA SISWA KELAS XI AKUNTANSI 2 SMK NEGERI 1 TANJUNG - Asniah Asniah (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2014)
Abstract. This research is motivated from three things, the delivery of materials science tends to be more focused on the provision of information or storytelling concepts on literature, so that students are less involved during the learning activities. This interest and motivation to learn science be reduced. Secondly, classical completeness is below standard, this is due to less pahamnya concepts that are presented. Third, students are less given the existing problems surrounding environment so that students are less concerned about the environment dirty. There are 3 formulation of the issues raised in this study, namely: how to increase the activity of students in learning, improve student learning outcomes and student response to learning on the competence to process waste. Using the model of Problem Based Learning objective of the research is to increase the activity of students, improve learning outcomes and evaluate the response of a class XI student of Accounting 2 SMKN 1 Tanjung on waste management competence. The results showed that the activity of students increased from a category quite the first cycle to the excellent category in the second cycle, the learning outcomes of students increased this can be seen from the students' understanding of the category enough the first cycle to the excellent category in the second cycle, the increased ability to solve problems from category enough in the first cycle to the excellent category in the second cycle, social skills increased from enough categories in the first cycle to be very good in the second cycle, skill performance increase of category enough the first cycle to the excellent category on the second cycle, the model learning Problem Based learning received a very positive response from the students of class XI AK 2 SMKN 1 Tanjung.Keywords: Problem Solving, Garbage, Problem Based Learning (PBL).